Synthesis and Characterization of Ester Based Azo-Benzene onto the Gold Nanoparticle Surfaces and Their Photo-Switching Ability - Kumar Biswas, Tapan; Mohd Yusoff, Mashitah; Lutfor Rahman, Md. (International Journal of Engineering and Technology, 2018)
In this paper we have synthesized p-substituted thiol terminal azobenzene liquid crystal embedded with gold nanoparticles and also observed their photoisomerization properties. Different thermal and spectroscopy techniques are used to investigate the synthesized compound properties. The gold nanoparticles surfaces attached thiolated ligand molecules (compound 4) exhibited smecticA phase. In solution, the synthesized compound shows strong photochromic behaviour. The photosaturation occurred around 9.3 second for compound 4 which indicated trans-to-cis conversion completely, whereas back relaxation due to cis-to-trans takes place at 576 minutes. Moreover, the delay back relaxation phenomenon gives us information about storage devices applicability. So, this study might be enhancing the molecular switches application and also be improved the knowledge in the fabrication of optical storage devices.Â Â